Peran Penyuluh Agama Hindu Dalam Pendidikan Karakter Generasi Muda Di Kabupaten Barito Selatan - Setiawan, Melky; Astawa, I Nyoman Sidi; L.Sigai, Ervantia Restulita (Dharma Duta, 2022)
The moral crisis is no longer a simple case but has serious consequences for the students, meanwhile to build a developed country it is necessary to have a young generation with noble character and character. This personality case can be seen from the existence of student brawls, juvenile delinquency, crime among young people, and so on. The phenomenon that occurs in several areas in South Barito Regency proves that this character education crisis also occurs in the region where juvenile delinquency is rampant and has entered the realm of crime. The role of Hindu religious instructors in character education for the younger generation in South Barito Regency is to teach knowledge about religious teachings and train religious skills. To do this, Hindu religious instructors also guide and motivate the younger generation to be diligent and study hard and be involved in the activities carried out. Hindu religious instructors also set an example for the younger generation in appearance and behavior in accordance with the teachings of goodness. The role of the Hindu religious instructor is to bring about a change in the character of the young generation of Hindus in South Barito Regency for the better.